The Mesozoic structural evolution of the Gorgon Platform, North Carnarvon Basin, Australia - Yang, X.; Elders, Chris (Taylor & Francis Co Ltd, 2016)
© 2016 Geological Society of Australia.The Gorgon Platform is located on the southeastern edge of the Exmouth Plateau in the North Carnarvon Basin, North West Shelf, Australia. A structural analysis using three-dimensional (3D) seismic data has revealed four major sets of extensional faults, namely, (1) the Exmouth Plateau extensional fault system, (2) the basin bounding fault system (Exmouth Plateau–Gorgon Platform Boundary Fault), (3) an intra-rift fault system in the graben between the Exmouth Plateau and the Gorgon Platform and (4) an intra-rift fault system within the graben between the Exmouth Plateau and the Exmouth Sub-basin. Fault throw-length analyses imply that the initial fault segments, which formed the Exmouth Plateau–Gorgon Platform Boundary Fault (EG Boundary Fault), were subsequently connected vertically and laterally by both soft- and hard-linked structures. These major extensional fault systems were controlled by three different extensional events during the Early and Middle Jurassic, Late Jurassic and Early Cretaceous, and illustrate the strong role of structural inheritance in determining fault orientation and linkage. The Lower and Middle Jurassic and Upper Jurassic to Lower Cretaceous syn-kinematic sequences are separated by unconformities.